LITERATUR REVIEW : SUMBER DAYA MANUSIA RUMAH SAKIT DALAM EKONOMI SAAT PANDEMI COVID 19 MELANDA INDONESIA - Aminulloh Aminulloh; Pudji Astuty (ITB Swadharma, 2021)
This shortage of human resources in health-care hospitals affects the national health system, but there is little research on how these HR issues affect medical workers. Understanding the impact on the health conditions of medical personnel is very important in the midst of the COVID-19 outbreak that is still sweeping the world. With the empirical literature, we have succeeded in summarizing the impact of the role and function of HR on the health of medical personnel. This study confirms that the role and function of human resources is transmitted to medical personnel through several models: (1) decreasing the quality of health services; (2) the impact of inadequate service measures; and (3) increasing demand for health services from patients; (4) A wave of public protests for treatment; (5) service and budget inefficiency